Efficient synthesis of well-defined cyclic polystyrenes using anionic polymerization, silicon chloride linking chemistry and metathesis ring closure. Issue 37 (7th September 2016) - He, Qiming; Yol, Aleer M.; Wang, Shih-Fan; Ma, Hongwei; Guo, Kai; Zhang, Fan; Wesdemiotis, Chrys; Quirk, Roderic P.; Foster, Mark D.
Abstract : An efficient method for the synthesis of well-defined cyclic polystyrenes using anionic polymerization, silicon chloride linking chemistry, and metathesis ring closure has been developed. Abstract : An efficient method for the synthesis of well-defined cyclic polystyrenes using anionic polymerization, silicon chloride linking chemistry, and metathesis ring closure has been developed. The macrocycle precursor, α, ω-bis(4-pentenyl)polystyrene, was formed by 4-pentenyllithium-initiated polymerization of styrene, coupling of α-pentenylpoly(styryl)lithium (PLi) with dimethyldichlorosilane to form α, ω-bis(4-pentenyl)polystyrene ( M n = 4600 g mol −1 ) and reaction of excess PLi with ethylene oxide to facilitate purification. Cyclization of the purified α, ω-bis(4-pentenyl)polystyrene was performed in dichloromethane under mild conditions using a Grubbs catalyst, bis(tricyclohexylphosphine)benzylidine ruthenium(iv ) chloride, as a metathesis ring-closure agent. In contrast to prior work, no fractionation is required to obtain the pure product. Both the divinyl precursor and resulting macrocycle were characterized by SEC, MALDI-TOF mass spectrometry (MS) and NMR. The macrocycle was unambiguously distinguished from its precursor using the fragmentation patterns from tandem mass spectrometry (MS 2 ) experiments. The results show that the macrocyclic precursor, α, ω-bis(4-pentenyl)polystyrene, was of high purity and that the cyclization was highly efficient.